EFEKTIVITAS MODEL THINK PAIR SHARE DISERTAI FLIPBOOK TERHADAP HASIL BELAJAR PADA MATERI PROTISTA - Kusumawardani, Ellyn; Panjaitan, Ruqiah Ganda Putri; ., Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
The purpose of this research is to determine effectiviness of TPS model accompained by flipbook media to ward study result at material Protista in class X SMA Negeri 1 Sanggau Ledo. The research was a Quasy Experimental with Nonequivalent control group design. The sample of this research are XE as experiment class and XB as control class. The instrument been used was multiple choice test that consists of 20 items. Average study result that had been TPS model accompained by flipbook media 15,03 was higher by those using conventional teaching 13,90. The U Mann Whitney test obtained Zcount< -Ztable that is -2,52 < -1,96, meaning that there were significant differences between study result that taught by TPS model accompained by flipbook media and conventional learning. Value of Effect Size obtained 0,48 is medium, meaning the use TPS model accompained by flipbook media effectively improve study result at material protista. Keywords: Cooperative Learning, Flipbook Media, Study Result.